2019
DOI: 10.1002/cbin.11115
|View full text |Cite
|
Sign up to set email alerts
|

Role of allograft inflammatory factor‐1 in the regulation of inflammation and oxidative stress in primary peritoneal mesothelial cells

Abstract: Peritoneal dialysis (PD) is often used to treat patients with end stage renal disease, and its long-term complications include excessive inflammation and oxidative stress. Allograft inflammatory factor 1 (AIF-1), as a cytoplasmic protein, is originally identified from infiltrating macrophages, and it was associated with inflammation in the cells other than macrophages, such as endothelial cells and vascular smooth muscle cells. To clarify the molecular mechanisms of AIF-1-modulated pathological changes in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…Several pathogen recognition proteins that could recognize the bacteria and initiate this response were modulated in the transcriptome (Saco et al, 2020) and were identified but not modulated in the proteome: fibrinogen-like proteins or FREPs, different types of lectins, C1-q containing proteins, and allograft inflammatory factor-1 (AIF-1). AIF-1 is a pro-inflammatory cytokine implicated in immune activation in molluscs (De Zoysa et al, 2010;Zhang et al, 2013) and can activate the NF-kB response (Egaña-Gorroño et al, 2019;Zhou et al, 2019). Immune recognition and signaling terms dominated the modulated response in the transcriptomic study of the same infection model, but they were not modulated in the current proteomic approach.…”
Section: Discussionmentioning
confidence: 83%
“…Several pathogen recognition proteins that could recognize the bacteria and initiate this response were modulated in the transcriptome (Saco et al, 2020) and were identified but not modulated in the proteome: fibrinogen-like proteins or FREPs, different types of lectins, C1-q containing proteins, and allograft inflammatory factor-1 (AIF-1). AIF-1 is a pro-inflammatory cytokine implicated in immune activation in molluscs (De Zoysa et al, 2010;Zhang et al, 2013) and can activate the NF-kB response (Egaña-Gorroño et al, 2019;Zhou et al, 2019). Immune recognition and signaling terms dominated the modulated response in the transcriptomic study of the same infection model, but they were not modulated in the current proteomic approach.…”
Section: Discussionmentioning
confidence: 83%
“…AIF-1 is an allograft inflammatory factor and plays an important role in regulating the inflammatory response. Our previous studies have confirmed that it is involved in the regulation of inflammatory reactions in various tissues and organs, including peritoneum [58], kidney [59], and blood vessels [37]. Although increasing evidence has confirmed that AIF-1 contributes to the pathogenesis of DKD [38,60], the exact mechanism is still unclear.…”
Section: Discussionmentioning
confidence: 96%
“…As the spatial conformation of AIF-1 is changed, which could activate several pathological processes, such as inflammation, apoptosis, and oxidative stress ( 25 , 26 ). It was reported that overexpression of AIF-1 in HUVEC could lead to endothelial cell inflammation and oxidative stress through the NF-κB signaling pathway ( 27 ). And the increased level of AIF-1 in VSMCs, induced by external stimulation, could also enhance the expression of cyclin and skeleton protein, thus leading to cell migration and phenotypic transformation, atherosclerosis, and vascular inflammation ( 16 ).…”
Section: Discussionmentioning
confidence: 99%